(untitled) (Bangladesh Journal of Pharmacology, 2017)
The prevention and treatment of the cancer using plants have attracted increasing interest. The present study was aimed to determine the phenolic compounds of Genista ferox using HPLC-TOF/MS and the anti-oxidant acti-vity associated with anti-cancer activity against human cervical adenocarcinoma (HeLa) cell line. Total anti-oxidant capacities of different extracts of G. ferox were assessed by DPPH assay, and their total phenolic and flavonoids contents measured by FolinCiocalteu and aluminum trichloride assays. The amounts of total phenolic (105.2 ± 0.6 308.5 ± 5.7 mg/g) of extract measured as gallic acid equivalent and flavonoids (8.1 ± 0.1 124.0 ± 0.7 mg/g) of extract measured as quercetin equivalent varied from chloroform to n-butanol extract of the two parts of the plant (leaf and stem). The ethyl acetate extract of G. ferox exhibited the most powerful effect on the DPPH scavenging activity with 94% from the leaf and 93% from the stem, while the chloroform extract from the leaf exhibited the most effective anti-proliferative activity against HeLa cell lines. Video Clip of Methodology: 4 min 6 sec Full Screen Alternate